Academic Expectancy Stress and Mental Toughness of Senior High School Students in a Catholic School - Matutino, Carmelo Renault B.; Singson, Deborah Natalia E. (Philippine Social Science Journal, 2020)
Academic expectancy stress is an unpleasant psychological situation due to educational expectations from parents, teachers, peers, and family members, educational systems, examinations, and the burden of homework. In this process, the students try to work hard to achieve high results. If they fail, they experience academic expectancy stress. Mental toughness is one of the essential concepts in psychology, which describes one’s ability to cope with pressure, stressors, and challenges. Hence, the paper describes the degree of academic expectancy stress and degree of the mental toughness of senior high school honor students enrolled in a Catholic School in Negros Occidental for the Academic Year 2019-2020. Likewise, it explores the difference between the students’ academic expectancy stress, mental toughness, and demographics. Lastly, it determines the correlation between academic expectancy stress and the mental toughness of honor students.